Impact evaluation of a cluster program: An application of synthetic control methods - Diego Aboal; Gustavo Crespi; Marcelo Perera (Inter-American Development Bank (IDB), 2017)
This paper analyzes the impact of a cluster tourism policy in the region of Colonia, Uruguay. The policy was implemented as part of an IDB-supported program. The study conducted a comparative analysis of Colonia vs. other tourism regions of the country applying a synthetic control method. This method of identifying the counterfactual is especially useful in comparative case studies where there are a limited number of control units. This is the first time that the synthetic control method has been applied to a cluster policy. The estimations show a positive impact of the cluster program on the inflow of international tourists to Colonia of 30 percent in the period 2008-2015; however, no significant impact on total expenditure was found.
Keywords: H43; O25; O54; R10; 330; cluster policy; impact evaluation; synthetic control methods